The impact of type d personality on health-related quality of life in patients with symptomatic haemorrhoids - Sit, Mustafa; Yilmaz, Edip Erdal; Canan, Fatih; Yildirim, Osman; Cetin, Mehmet Mustafa (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction: Haemorrhoids are one of the most common reasons that patients seek consultation from a colon and rectal surgeon. Health-related quality of life (HrQoL) is a significant factor in describing the burden of illness and the impact of treatment in patients with gastrointestinal disease. Type D (distressed) personality is defined as the co-occurrence of negative affect and social inhibition. Aim : To assess the prevalence of type D personality in patients with haemorrhoids and to investigate whether the presence of a type D personality would affect HrQoL in patients with haemorrhoids. Material and methods : One hundred and six outpatients with symptomatic haemorrhoids with no psychiatric comorbidity were consecutively enrolled, along with 96 healthy controls. The Type D Scale (DS14) and the General Health Survey Short Form-36 (SF-36) were used in the collection of data. Results: Of 106 patients evaluated, 29.2% met criteria for type D personality. Patients with haemorrhoids scored lower on bodily pain and vitality dimensions of SF-36 than did healthy subjects (p < 0.001). Patients with a type D personality were found to score lower on bodily pain domain of HrQoL than patients without a type D personality. Linear regression analysis revealed a significant independent association of type D personality with bodily pain dimension of the SF-36 in patients with symptomatic haemorrhoids (r = –0.315, p < 0.01). Conclusions : Type D personality was associated with increased perceived bodily pain in patients with haemorrhoids. Consideration of type D personality construct personality traits could improve risk stratification in research and clinical practice in this patient group.